PENERAPAN HYGIENE DAN SANITASI DI INSTALASI GIZI RUMAH SAKIT UMUM PUSAT (RSUP) Dr. M. DJAMIL PADANG - Adhini W, Dwi Mustika; Elida, Elida; Syarif, Wirnelis (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
The study aims to document and determine the application of hygiene dan sanitation in nutrient installation Dr. M. Djamil Padang of the application which includes personal hygiene, environmentl hygiene, food hygiene dan sanitary facilities. This research uses a qualitative approaches, the technique collection technique of observation, interviews and documentation. Validity of data do creadibility test, transferability test, dependability test, and test confirmability. Analyzed the data reduction, data presentation and withdrawal conclusions or verification.The results showed that : overall Application of hygiene and sanitation in nutrient installation has not been done optimally viewed from of personal hygiene, of environmental hygiene food hygiene and the sanitary facilitiesKeyword: Hygiene and Sanitation, Nutrient Installation